Meningkatkan Minat Membaca pada Anak SD Melalui Perpustakaan Mini di Lingkungan Masyarakat - Nidya Putri Syahida; Vidya Yanti Utami; Siti Hidayatul Jumaah; Nasruddin Nasruddin; Fitriah Kartini (Jurnal Pengabdian Bersama Masyarakat Indonesia, 2025)
The interest in reading in Indonesia is still relatively low according to various international surveys, so it needs to be a shared concern so that it does not have a negative impact in the future. This community service aims to increase the interest in reading of elementary school children in Brambang village through a mini library program. Low access to interesting and educational reading books is one of the main challenges in fostering a reading culture among children. This activity involves the procurement and management of a mini library equipped with a collection of books on various themes, including fairy tales, science, and inspirational stories. In addition, supporting activities such as storytelling, reading competitions, and basic literacy training are held to attract children's interest. This program is carried out collaboratively by involving the local community, parents, and volunteers. The results of the activity show an increase in children's enthusiasm for reading books, which can be seen from the increasing number of visits to the mini library and active participation in literacy activities. This program is expected to be the first step in building a sustainable literacy culture in Brambang village and can be the starting point.